Reading ʿAttār’s Elāhināma as Sufi Practical Ethics: Between Genre, Reception, and Muslim and Christian Audiences - Dabiri, Ghazzal (Journal of Persianate studies, 2018)
Abstract This paper seeks to contribute to the field of reception and audience studies by analyzing ʿAttār’s Elāhināma. Little studied, the Elāhināma offers an opportunity to understand better ʿAttār’s attitudes towards socio-religious issues, as well as the types of audiences that the text seeks, how it addresses them, and what possible aims it has. The paper argues that the Elāhināma mobilizes the formal characteristics of practical ethics and mirrors while disrupting them at the level of meaning towards its own aims, namely, a just society grounded in the tenets of Sufism, for a broad, non-specialized audience, which also includes Christians and Muslims. The paper analyzes and discusses not only the structure of the overall text, but also the first story, the “Tale of the Virtuous Woman,” which sets the tone. This story is an interesting case since it resembles the way that lives of female Byzantine Christian saints are constructed. It thus offers an opportunity to comment on the itinerant nature of narratives across Eurasia and more specifically the types of tales circulating in medieval eastern Iran.